The Relationship between Parenting Patterns and Gross Motor Development in Pre-School Children - Huda Rohmawati; Nara Lintan M. P.; Agung Widhi N.; Dewi Afifi (Journal of Global Research in Public Health, 2023)
Development is psychological change as a result of the process of maturation of psychological and physical functions in children, which is supported by environmental factors and the learning process over a certain period of time towards maturity. The purpose of this study was to determine the relationship between parenting patterns and gross motor development in pre-school children at TKIT Bina Insani, Mojoroto District, Kediri. The design of this research is correlation analytic. The population in this study were all parents and pre-school children at Bina Insani Islamic Kindergarten. In accordance with predetermined research criteria, In accordance with predetermined research criteria, a sample of 48 respondents was obtained. The results of data analysis using the Fisher’s Exact Test show that p-value = 0.000 at α = 0.05, because p-value < α then H0 is rejected and H1 is accepted, which means there is a relationship between sharpening patterns and gross motor development in pre-school children in TKIT Bina Insani, Mojoroto District, Kediri. It is hoped that we can develop outreach to parents so that parents can develop honing patterns that suit the child’s needs so that the child’s gross motor development can run well.